2000
DOI: 10.1542/peds.106.6.1318
|View full text |Cite
|
Sign up to set email alerts
|

Baby CareLink: Using the Internet and Telemedicine to Improve Care for High-Risk Infants

Abstract: CareLink significantly improves family satisfaction with inpatient VLBW care and definitively lowers costs associated with hospital to hospital transfer. Our data suggest the use of telemedicine and the Internet support the educational and emotional needs of families facilitating earlier discharge to home of VLBW infants. We believe that further extension of the Baby CareLink model to the postdischarge period will significantly improve the coordination and efficiency of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(110 citation statements)
references
References 3 publications
2
102
0
3
Order By: Relevance
“…One study demonstrated improvements in length of hospitalization and quality of care received in the neonatal ICU. 5 Gray et al 5 reported that infants ,1000 g enrolled in the videoconferencing program trended toward shorter length of stay (77.4 days vs 91.3 days), compared Our findings are also consistent with results found by other investigators using videoconferencing in the adult population. Chiang et al 13 reported that family caregivers of heart failure patients who received telenursing consultations experienced significant reductions in caregiver burden and stress and significant improvements in family function.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…One study demonstrated improvements in length of hospitalization and quality of care received in the neonatal ICU. 5 Gray et al 5 reported that infants ,1000 g enrolled in the videoconferencing program trended toward shorter length of stay (77.4 days vs 91.3 days), compared Our findings are also consistent with results found by other investigators using videoconferencing in the adult population. Chiang et al 13 reported that family caregivers of heart failure patients who received telenursing consultations experienced significant reductions in caregiver burden and stress and significant improvements in family function.…”
Section: Discussionsupporting
confidence: 89%
“…For example, it is increasingly common for health systems to facilitate virtual visits for parents and families with their children in the NICU and other inpatient wards using webcams or other mobile devices. [5][6][7] Such programs enable enhanced communication between patients, parents, families, and friends, hopefully improving the spirits and wellbeing of both those in the hospital as well as those who live far away or are unable to visit the hospital. However, despite the common use of these videoconferencing systems, little is known beyond anecdotal experience about their potential impact on the stress experienced by children during hospitalization.…”
mentioning
confidence: 99%
“…Home-based systems have been used in other pediatric venues, such as with critically ill newborns. 17,18 Links to community Community-based contact information for parents could be accessed through the resources web. It could also link parents with information about specific concerns.…”
Section: Home Visitsmentioning
confidence: 99%
“…One involved 17 parents whose babies had been discharged on average 8 months previously (Tang, Hirano, Cheng, & Hayes, 2012); the other involved four parents whose babies had been ''recently discharged'' (Lee, Garfield, Massey, Chaysinh, & Hassan, 2011). Besides our own work, we are aware of only two technology studies that have involved parents whose babies were in the NNU at the time of participation: One involved interviews with nine parents (Mahamood, Reiter, & Mellish, 2008) and the other an evaluation with 56 parents (J. E. Gray et al, 2000).…”
Section: Research With Parentsmentioning
confidence: 99%
“…For example, in their development and evaluation of Baby CareLink, a telemedicine application which provided tailored information and support to families of very low birth weight infants, Gray et al found that families varied in the amount of information that they wanted about their baby (Gray et al, 1998;Gray et al, 2000). Some families felt overwhelmed by the information that medical staff gave them about their sick baby; others wanted more information than they were given.…”
Section: Adaptive Ehealthmentioning
confidence: 99%